The complexity of architectural and anthropological dynamics in womb-tomb structures: An interdisciplinary investigation - Nurit Stadler; Shlomit Flint (PLoS ONE, 2025)
Our research investigates a collection of distinctive case studies identified as ‘womb-tomb sacred structures,’ scattered throughout the region colloquially referred to as the Holy Land. This geographical area, nestled between the Mediterranean Sea and the East Bank of the Jordan River, holds profound historical and religious significance, intersecting with the biblical Land of Israel and the broader region of Palestine. It is revered by followers of Judaism, Christianity, and Islam. This study offers a pioneering exploration of the complex interplay between human corporeal rituals at sacred sites and architectural forms, illuminating not only how these rituals impact architectural design but also how the design influences the rituals themselves. We have catalogued an extensive array of womb-tomb structures across this landscape, dating from various periods including the First and Second Temples (700 BCE) and the Byzantine era. Despite their chronological diversity, these structures share architectural characteristics—typically, they are enclosed, cave-like spaces, often dimly lit and surmounted by domes. The architectural geomorphology of the womb-tomb designs prescribes specific bodily movements, with their distinctive forms necessitating, and sometimes enforcing, actions such as bending, crawling, and bowing within these enveloping spaces. Our exploration is supported by a novel methodological framework consisting of nine stages, which harmoniously blends architectural analysis (including Spatial Analysis, Morphological Analysis, 4D Approach) with anthropological perspectives and methodologies (including observations, interviews, photographic documentation, and short films). Our results elucidate that these architectural structures and morphologies serve not merely as sanctified sites but also unveil previously unrecognized connections among human anatomy, architectural configurations of the afterlife, and the connections between ritualistic conceptualization of soil, land, and territory as expressions of ownership and power.